Establishment of a human-induced pluripotent stem cell line from a long QT syndrome type 2 patient harboring a KCNH2 mutation - Dasom Mun; Ji-Young Kang; Malgeum Park; Gyeongseo Yoo; Hyoeun Kim; Nuri Yun; You Mi Hwang; Boyoung Joung (Stem Cell Research)
Long QT syndrome type 2 (LQT2) is a heart disorder resulting from a loss-of-function mutation in the KCNH2 gene that causes loss of Kv11.1 channel function, potentially resulting in syncope, arrhythmias, and sudden death. We derived induced pluripotent stem cell line from PBMC of LQT2 patient carrying a variant of pathogenic variant (c.157G > A; p.Gly53Ser). The generation of iPSC lines was achieved using the non-integrative Sendai virus-mediated iPSC reprogramming method. The iPSC cell line exhibit pluripotency, normal karyotype, stem cell morphology, and differentiation capability, resulting a reliable cell source to study the effects of KCNH2 mutation in disease-specific cell types.